Hydrogen-bonded organic frameworks: design, structures and potential applications - Luo, Jie; Wang, Jia-Wei; Zhang, Ji-Hong; Lai, Shan; Zhong, Di-Chang (CrystEngComm, 2018)
Hydrogen-bonded organic frameworks (HOFs), a new type of porous material following the metal-organic frameworks (MOFs), covalent organic frameworks (COFs), etc. , have emerged as one of the promising candidates in diverse potential applications. In this highlight, we summarize the key progress on HOF-based materials, in which their design, structures, as well as potential applications will be discussed. This paper highlights the current key progress on HOF-based materials, including their design, structural characteristics, and applications.